Colubrina arborescens Coffee Colubrina, Wild Coffee: FPS137/FP137, 5/2007 - Gilman, Edward (EDIS, 2007)
This document provides an overview of Colubrina arborescens, commonly known as coffee colubrina or wild coffee. Native to south Florida and the Caribbean Basin, this small tree or large shrub can reach heights of 20 feet or more. It features shiny, dark green leaves with prominent yellow veins and rust-colored hairs. The plant thrives in sunny or partially shaded locations and is suitable for various uses, including as a hedge, screen, or ornamental plant. It is highly drought-tolerant, grows well in various soil types, and is not known to be invasive. The document also highlights its year-round flowering, bird-attracting fruit, and general pest resistance.Original publication date October 1999.